PELATIHAN ECOPRINT DENGAN TEKNIK POUNDING UNTUK SISWA-SISWI SEKOLAH DASAR DI WILAYAH DESA BATURITI TABANAN BALI - Sri Utami; Vita Wulansari; I Gusti Agung Malini; Pande Putu Wiweka Ari Dewanti; Elivia Wardani; , Masdalipa; Elizabeth Engelina Iskandar; Wayan Oka Winiati; I.G.B Bayu Baruna Ariesta; I G. Agung Ayu Widyandari Kameswari (LPPM Institut Desain dan Bisnis Bali, 2023)
Baturiti Village is one of the villages in the Tabanan district of Bali where the majority of the people work as vegetable and fruit farmers as one of the leading commodities in the region. The potential possessed by Baturiti Village is natural resources such as rice fields, agricultural land, plantations and as a river basin so that it becomes a very fertile area and produces many natural resources such as various kinds of vegetables so that Baturiti becomes one of the leading agro-tourism areas in the Tabanan district. Bali. Baturiti Village is located in a highland area with a very beautiful atmosphere with rice fields and plantations and there are various kinds of plants that grow very fertile. The biological riches originating from the natural resources of Baturiti village have not been fully utilized by the community, so on this occasion we from the IDB Bali Fashion Design lecturer and student team conducted an exploration which was implemented into the Community Service program and implemented in several schools, especially Elementary Schools (SD). ) and Junior High Schools (SMP) in the Baturiti area in the form of an Eco Print training program with Pounding Techniques for female students as one of the P5 program materials (Strengthening Pancasila Student Profile Program). Ecoprint is a technique for printing, coloring and making products using natural materials such as plants, both leaves and flowers. In the process of making ecoprints, several media are needed, such as cloth, plastic, wooden hammers and alum stone. The aim of this activity is to train students' sensitivity to the natural environment and foster students' creativity and skills to make products that are useful and environmentally friendly.